Rapid repair of DNA double strand breaks in Arabidopsis thaliana is dependent on proteins involved in chromosome structure maintenance - Kozak, Jaroslav; West, Christopher E; White, Charles; da Costa-Nunes, José A; Angelis, Karel J (DNA repair, 2009)
DNA double strand breaks (DSBs) are one of the most cytotoxic forms of DNA damage and must be repaired by recombination, predominantly via non-homologous joining of DNA ends (NHEJ) in higher eukaryotes. However, analysis of DSB repair kinetics of plant NHEJ mutants atlig4-4 and atku80 with the neutral comet assay shows that alternative DSB repair pathways are active. Surprisingly, these kinetic measurements show that DSB repair was faster in the NHEJ mutant lines than in wild-type Arabidopsis. Here we provide the first characterization of this KU-independent, rapid DSB repair pathway operating in Arabidopsis. The alternate pathway that rapidly removes the majority of DSBs present in nuclear DNA depends upon structural maintenance of chromosomes (SMC) complex proteins, namely MIM/AtRAD18 and AtRAD21.1. An absolute requirement for SMC proteins and kleisin for rapid repair of DSBs in Arabidopsis opens new insight into the mechanism of DSB removal in plants.
Keywords: proteiny huseníčku; Chromosomal Proteins, Non-Histone; protinádorová antibiotika; Comet Assay; Arabidopsis; fragmentace DNA; vztah mezi dávkou a účinkem léčiva; Arabidopsis Proteins; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; chromozomy rostlin; Chromosomes, Plant; DNA rostlinná; DNA Repair; Time Factors; oprava DNA; bleomycin; DNA, Plant; DNA Fragmentation; Recombination, Genetic; kometový test; Antibiotics, Antineoplastic; časové faktory; rekombinace genetická; Bleomycin; chromozomální proteiny, nehistonové; Dose-Response Relationship, Drug